The Development of Thai L1 Grade 4 Students’ Spelling Skills Using the Integrated Explicit Instruction and Metacognition Exercises - Supapong Boonsad; Authhapon Intasena (Journal of Educational Issues, 2024)
The purposes of the current study were 1) to investigate the effectiveness of the integrated explicit instruction and metacognition exercises on Thai L1 grade 4 students’ spelling skills, 2) to compare Thai L1 grade 4 students’ spelling skills before and after using the integrated explicit instruction and metacognition exercises, and 3) to study students’ satisfaction toward the integrated explicit instruction and metacognition exercises. The participants were 42 4th grade primary school students in Thailand selected by the purposive sampling method. The instruments were a set of spelling exercises designed using the integration of explicit teaching and metacognitive instruction, a pre-posttest, and a questionnaire. The data were analyzed using percentage, mean score, standard deviation, a paired samples t-test, and the effectiveness index with the criterion of 80. The results of the study indicate that 1) the effectiveness of the integrated explicit instruction and metacognition exercises on Thai L1 grade 4 students’ spelling skills was at 84.57/83.97 reaching the criteria of 80, 2) the students’ score after learning with the integrated explicit instruction and metacognition exercises was significantly higher than students’ score before the treatment at a statistical level of .05, and 3) students’ satisfaction toward the integrated explicit instruction and metacognition exercises was at a very high level (x̄ = 4.53, S.D. = 0.52). The result of the study could be implicated in both pedagogic and academic aspects.